Left atrium stress echocardiography: correlation between left atrial volume, function, and B-lines at rest and during stress - Costantina Prota; Lauro Cortigiani; Ettore Campagnano; Karina Wierzbowska-Drabik; Jaroslaw Kasprzak; Paolo Colonna; Elisa Merli; Fiore Manganelli; Nicola Gaibazzi; Antonello D’Andrea; Emma Cerracchio; Laura Meola; et al. (Exploration of Cardiology, 2024)
Aim: Left atrial volume index (LAVI), left atrial reservoir function through left atrial reservoir strain (LASr), and B-lines in lung ultrasound serve as supplementary indicators of left ventricular filling pressures. This study analyzes the interrelation between LAVI, LASr, and B-lines in both resting and peak vasodilator stress. Methods: Dipyridamole stress echocardiography (SE) was conducted on 252 individuals (180 males, 71%, age 65 years ± 10 years) with chronic coronary syndromes. LAVI was quantified using the biplane disk summation method; LASr was obtained using 2-dimensional speckle tracking echocardiography; B-lines were evaluated through a simplified 4-site scan in the third intercostal space during lung ultrasound. Results: During SE, a reduction in LAVI (26 ml/m2 ± 14 ml/m2 vs. 24 ml/m2 ± 12 ml/m2, P < 0.001) and an increase in LASr from rest (33% ± 8% vs. 38% ± 10%, P < 0.001) were respectively observed from rest to stress. B-lines were increased significantly during SE, from 19 (7.5%) to 29 (11.5%), P < 0.001. A substantial, inverse linear correlation was identified between LAVI and LASr both at rest (r = –0.301, P < 0.001) and peak stress (r = –0.279, P < 0.001). At group analysis, peak B-lines showed a direct correlation with peak LAVI (r = 0.151, P = 0.017) and an inverse correlation with peak LASr (r = –0.234, P < 0.001). In individual assessments, 9.7% (20/207) of patients displayed stress B-lines with normal LAVI and preserved LASr, while 20% (9/45) exhibited stress B-lines with abnormalities in both LAVI and LASr. Conclusions: Vasodilator SE with combined left atrial and volume assessment, related to pulmonary congestion, is feasible with a high success rate. Pulmonary congestion is more frequent with dilated left atrium with reduced atrial contractile reserve (ClinicalTrials.gov identifier: NCT030.49995; NCT050.81115).